Evolution of Tick-Borne Encephalitis over an 80-year Period: Main Manifestations, Probable Causes - N. M. Kolyasnikova; S. G. Gerasimov; A. A. Ishmukhametov; V. V. Pogodina (Эпидемиология и вакцинопрофилактика, 2020)
In this review, the manifestations of the tick-borne encephalitis (TBE) evolution in different aspects, which are traced over the 80 years since the discovery of TBE virus, are highlighted and systematized. The evolution of infection is expressed in a change in the properties of the etiological agent (changing of the genetic structure of the pathogen populations in certain territories, phenomenon of changing in the dominant subtype, changing in virulence), the epidemiology and ecology of TBE (period of marked increase in incidence, changing in the endemicity of territories, level of population immunity, the appearance of foci TBE in suburban areas and cities, changing in the range of certain types of ticks and the appearance of «tick-mutants»), as well as the clinical picture of TBE (phenomenon of pathomorphosis, growing relevance of mixed infections transmitted by ticks). The analysis of the possible causes of evolutionary transformations is carried out, among which the main ones are natural factors (climate change), anthropogenic factors, namely disturbance of natural landscapes due to human activities and environmental pollution by some pesticides, and additional ones -impact of vaccination. Purpose of the article: characteristics of the main manifestations and probable causes of the evolution of TBE over 80 years. Conclusions: The review for the first time provides information about the main issues of this problem, identifies changes and transformations that affect pathogens and vectors, and, as a result, entails changes in the epidemiology and clinical picture of this disease, which are traced in different territories.